Composite PBO fiber, composite skeleton, preparation method of composite skeleton, composite membrane, preparation method of composite membrane and application of composite membrane
By preparing composite PBO fibers and conductive coatings, the problem that existing EMI shielding materials are difficult to prevent cold and electromagnetic interference at the same time in harsh environments is solved, and efficient electromagnetic shielding and thermal management performance is achieved, which is suitable for smart wearable electronic products.
Patent Information
- Application Number
- CN202411813587.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-11
AI Technical Summary
Existing EMI shielding materials are difficult to prevent cold and electromagnetic interference at the same time in harsh environments such as polar regions or outer space, and lack versatility to meet the needs of smart wearable electronic products.
By preparing composite PBO fibers, including PBO fibers and polybenzophenone-type benzoxazines coated on the surface of PBO fibers, a conductive coating is formed by combining graphene nanosheets and carbon nanotubes to form a conductive coating, thereby improving the dispersion and thermal conductivity of the material.
It realizes efficient electromagnetic shielding, personal thermal management and heating performance of materials, and is suitable for electronic devices in harsh environments such as polar regions or outer space.
Smart Images

Figure CN119571605A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of composite membranes, and in particular to a composite PBO fiber, a composite skeleton and a preparation method thereof, a composite membrane and a preparation method and application thereof. Background Art
[0002] Communication equipment and wearable electronic devices have experienced explosive growth, and the resulting electromagnetic wave radiation inevitably poses a threat to human health. EMI shielding materials play a vital role in protecting sensitive electronic devices and maintaining human health by shielding external electromagnetic interference (EMI) and radiation. EMI shielding materials are usually designed to have high EMI shielding effectiveness, be lightweight and easy to produce. However, these materials need to have more functions for practical applications, which has been overlooked. In harsh environments such as low temperature and high electromagnetic radiation in the polar regions or outer space, electronic devices should be protected from both cold and electromagnetic interference to ensure working efficiency. Therefore, the development of multifunctional devices with electromagnetic shielding, personal thermal management and heating performance is highly desirable for smart wearable electronic products.
[0003] It is well known that graphene nanosheets (GnPs) have good thermal conductivity, which can be as high as 5000 W·m -1 ·K -1 . In addition, GnPs also have excellent light / electrothermal conversion properties, which makes GnPs an ideal choice for preparing heaters and thermal management materials. Carbon nanotubes (MWCNTs) have a unique spatial structure that allows electrons and phonons to move quickly in their direction and reduce scattering, so they have excellent thermal properties, mechanical properties, and excellent thermal conductivity. MWCNTs (rod-shaped) are introduced into GnPs, which can act as a bridge between graphene sheets, facilitating electron transport and stress transfer. In addition, GnPs can also form conductive paths at line-to-line joints to improve resistance uniformity. However, MWCNTs and GnPs lack functional groups and therefore have poor dispersibility in the substrate resin. Summary of the invention
[0004] The invention provides a composite PBO fiber, a composite skeleton and a preparation method thereof, a composite membrane and a preparation method and application thereof. The composite PBO fiber of the invention can improve the dispersibility of MWCNTs and GnPs in a matrix resin.
[0005] The invention provides a composite PBO fiber, comprising a PBO fiber and a polybenzophenone-type benzoxazine coated on the surface of the PBO fiber.
[0006] The present invention also provides a composite skeleton, comprising the composite PBO fiber described in the above technical solution and the conductive coating on the surface of the polybenzophenone-type benzoxazine;
[0007] The conductive coating includes graphene nanosheets and carbon nanotubes.
[0008] The present invention also provides a method for preparing the composite skeleton described in the above technical solution, comprising the following steps:
[0009] The surface of the PBO fiber is treated with plasma to introduce hydroxyl groups on the surface of the PBO fiber to obtain PBO-OH fiber;
[0010] The PBO-OH fiber, benzophenone-type benzoxazine and an organic solvent are first mixed, and the benzophenone-type benzoxazine is adsorbed on the surface of the PBO-OH fiber to obtain a first mixture;
[0011] The first mixture is mixed with graphene nanosheets and carbon nanotubes, and the graphene nanosheets and carbon nanotubes are adhered to form a conductive coating to obtain a PBO-OH fiber containing a conductive coating and benzophenone-type benzoxazine;
[0012] The PBO-OH fiber containing the conductive coating and benzophenone-type benzoxazine is thermally cured to obtain the composite skeleton.
[0013] Preferably, the mass ratio of the PBO-OH fiber to the benzophenone-type benzoxazine is 1:0.25-12.5.
[0014] Preferably, the mass ratio of the graphene nanosheets to the carbon nanotubes is 1:0.1-1.
[0015] Preferably, the thermal curing temperature is 130-210° C. and the time is 0.5-2 h.
[0016] The present invention also provides a composite membrane, comprising a matrix and a composite skeleton dispersed in the matrix;
[0017] The matrix includes fluorinated polyetheretherketone and polyetheretherketone;
[0018] The composite skeleton is the composite skeleton described in the above technical solution or a composite skeleton prepared by the preparation method described in the above technical solution.
[0019] Preferably, the ratio of the mass of the conductive coating in the composite film to the mass of the composite film minus the mass of the polybenzophenone-type benzoxazine is 0.05-0.35:1.
[0020] The present invention also provides a method for preparing the composite membrane described in the above and similar schemes, comprising the following steps:
[0021] Repeatedly mixing the composite skeleton with the dispersion of the matrix and then removing the solvent in the dispersion to obtain a composite;
[0022] The composite is formed into a shape to obtain the composite film.
[0023] The present invention also provides the application of the composite film described in the above technical solution or the composite film prepared by the preparation method described in the above technical solution in thermal management.
[0024] The hydroxyl groups of polybenzophenone-type benzoxazine in the composite PBO fiber can form hydrogen bonds with the carbonyl groups in PEEK, which weakens the interfacial thermal resistance between the polymer and the carbon nanofiller (graphene nanosheets and carbon nanotubes) and increases the interfacial compatibility. In addition, the hydrogen bonding effect also effectively reduces the p-p stacking between the carbon nanofillers (graphene nanosheets and carbon nanotubes), improves the dispersibility of the carbon nanofillers (graphene nanosheets and carbon nanotubes), and improves the thermal conductivity of the composite film prepared using the composite PBO fiber, graphene nanosheets and carbon nanotubes.
[0025] The introduction of polybenzophenone-type benzoxazine reduces the interfacial thermal resistance problem, improves the thermal conductivity of the composite material, and constructs a composite skeleton with a continuous structure (graphene nanosheets and carbon nanotubes form a conductive coating), thereby improving the electromagnetic shielding performance of the composite material.
[0026] The graphene nanosheets and carbon nanotubes introduced into the composite film of the present invention can significantly improve the electrical conductivity and electromagnetic shielding performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Flow chart of preparing MWCNTs&GnPs@PBO-PBZ / PEEK composite membrane material for example;
[0028] Figure 2 The thermal conductivity results of the MWCNTs&GnPs@PBO-PBZ / PEEK composite film materials of Examples 1 to 7;
[0029] Figure 3 The thermal conductivity results of the MWCNTs&GnPs@PBO / PEEK composite film materials of Comparative Examples 1 to 7;
[0030] Figure 4 The EMI shielding performance results of the MWCNTs&GnPs@PBO-PBZ / PEEK composite film materials of Examples 1 to 7;
[0031] Figure 5 These are the Joule thermal performance results of the MWCNTs&GnPs@PBO-PBZ / PEEK composite membrane material of Example 7. DETAILED DESCRIPTION
[0032] The invention provides a composite PBO fiber, comprising a PBO fiber and a polybenzophenone-type benzoxazine coated on the surface of the PBO fiber.
[0033] The method for preparing the composite PBO fiber preferably comprises the following steps:
[0034] The surface of the PBO fiber is treated with plasma to introduce hydroxyl groups on the surface of the PBO fiber to obtain PBO-OH fiber;
[0035] The PBO-OH fiber, benzophenone-type benzoxazine and an organic solvent are first mixed, and the benzophenone-type benzoxazine is adsorbed on the surface of the PBO-OH fiber, and then thermally cured.
[0036] The present invention also provides a composite skeleton, comprising the composite PBO fiber described in the above scheme and a conductive coating located on the surface of the polybenzophenone-type benzoxazine;
[0037] The conductive coating includes graphene nanosheets and carbon nanotubes.
[0038] The present invention also provides a method for preparing the composite skeleton described in the above technical solution, comprising the following steps:
[0039] The surface of the PBO fiber is treated with plasma to introduce hydroxyl groups on the surface of the PBO fiber to obtain PBO-OH fiber;
[0040] The PBO-OH fiber, benzophenone-type benzoxazine and an organic solvent are first mixed, and the benzophenone-type benzoxazine is adsorbed on the surface of the PBO-OH fiber to obtain a first mixture;
[0041] The first mixture is mixed with graphene nanosheets and carbon nanotubes, and the graphene nanosheets and carbon nanotubes are adhered to form a conductive coating to obtain a PBO-OH fiber containing a conductive coating and benzophenone-type benzoxazine;
[0042] The PBO-OH fiber containing the conductive coating and benzophenone-type benzoxazine is thermally cured to obtain the composite skeleton.
[0043] The present invention performs plasma treatment on the surface of the PBO fiber, introduces hydroxyl groups on the surface of the PBO fiber, and obtains PBO-OH fiber.
[0044] In the present invention, before the plasma treatment, it is preferred to further include: removing the sizing agent and pollutants on the surface of the PBO fiber, and then drying and dispersing.
[0045] In the present invention, the removal preferably includes separating the PBO fibers by soaking them in acetone and water successively; the present invention has no particular limitation on the soaking time in acetone and water, as long as the sizing agent and contaminants are removed. In a specific embodiment of the present invention, the soaking time in acetone and water is 24 hours.
[0046] In the present invention, the drying temperature is preferably 60° C. and the drying time is preferably 4 hours.
[0047] In the present invention, the dispersion preferably comprises: immersing the dried PBO fibers in ethanol and then sequentially performing ultrasonic dispersion, separation and drying.
[0048] In the present invention, the discharge power of the plasma treatment is preferably 120W, the discharge time is preferably 300-400s, and in a specific embodiment of the present invention, the discharge time may be 300s, 310s, 320s, 330s, 340s, 350s, 360s, 370s, 380s, 390s or 400s; the pressure is preferably 30-50Pa, and in a specific embodiment of the present invention, the pressure may be 30Pa, 35Pa, 40Pa, 45Pa or 50Pa; O2 and A in the plasma treatment are preferably 120W, and the discharge time is preferably 300-400s, and in a specific embodiment of the present invention, the discharge time may be 300s, 310s, 320s, 330s, 340s, 350s, 360s, 370s, 380s, 390s or 400s; the pressure is preferably 30-50Pa, and in a specific embodiment of the present invention, the pressure may be 30Pa, 35Pa, 40Pa, 45Pa or 50Pa; r The volume ratio is preferably 1:0.2-1.5. In a specific embodiment of the present invention, the volume ratio can be 1:0.2, 1:0.5, 1:1 or 1:1.5.
[0049] The present invention utilizes plasma treatment to activate the surface of the PBO fiber, generates hydroxyl groups, and increases the roughness of the surface of the PBO fiber.
[0050] After obtaining the PBO-OH fiber, the present invention first mixes the PBO-OH fiber, benzophenone-type benzoxazine and an organic solvent, and the benzophenone-type benzoxazine is adsorbed on the surface of the PBO-OH fiber to obtain a first mixture.
[0051] In the present invention, the mass ratio of the PBO-OH fiber to the benzophenone-type benzoxazine is 1:0.25-12.5. In a specific embodiment of the present invention, the mass ratio of the PBO fiber to the benzophenone-type benzoxazine may be 1:0.25, 1:1, 14:25, 1:2, 1:0.25, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11 or 1:12.5.
[0052] In the present invention, the ratio of the mass of the benzophenone-type benzoxazine to the volume of the organic solvent is preferably 1g:20-80mL. In a specific embodiment of the present invention, the ratio of the mass of the benzophenone-type benzoxazine to the volume of the organic solvent may be 1g:20mL, 1g:40mL, 1g:60mL or 1g:80mL; the organic solvent preferably includes acetone.
[0053] In the present invention, the temperature of the first mixing is preferably 65-75°C, and the time is preferably 6-18h. In a specific embodiment of the present invention, the temperature of the first mixing can be 65°C, 70°C or 75°C, and the time can be 6h, 8h, 10h, 12h, 14h, 16h or 18h; the first mixing is preferably carried out under reflux conditions.
[0054] In the first mixing, the benzophenone-type benzoxazine, which contains nitrogen, is adsorbed on the surface of the PBO-OH fiber through hydrogen bonds with the hydroxyl groups on the PBO-OH fiber.
[0055] After obtaining the first mixture, the present invention mixes the first mixture with graphene nanosheets and carbon nanotubes, and the graphene nanosheets and carbon nanotubes form a conductive coating through the adhesion of benzophenone-type benzoxazine to obtain PBO-OH fibers containing the conductive coating and benzophenone-type benzoxazine.
[0056] In the present invention, the second mixing preferably includes: adding the graphene nanosheets and carbon nanotubes to the first mixture obtained after the first mixing is completed, and then cooling the mixture.
[0057] In the present invention, the mass ratio of the graphene nanosheets to the carbon nanotubes is preferably 1:0.1-1. In a specific embodiment of the present invention, the mass ratio can be 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1.
[0058] In the second mixture, graphene nanosheets and carbon nanotubes adhere to the PBO-OH fibers by virtue of the viscosity of benzophenone-type benzoxazine.
[0059] In the present invention, after the second mixing, the method preferably further comprises: separation to obtain the PBO-OH fibers adsorbed with graphene nanosheets, carbon nanotubes and benzophenone-type benzoxazine.
[0060] After obtaining the PBO-OH fiber containing the conductive coating and benzophenone-type benzoxazine, the present invention thermally cures the PBO-OH fiber containing the conductive coating and benzophenone-type benzoxazine to obtain the composite skeleton.
[0061] In the present invention, the temperature of the thermal curing is preferably 130-210° C., and the time is preferably 0.5-2 hours. In a specific embodiment of the present invention, the temperature of the thermal curing can be 130° C., 150° C., 170° C., 175° C., 190° C. or 210° C., and the time can be 0.5 hours, 1 hour, 1.5 hours or 2 hours. Benzophenone-type benzoxazine generates polybenzophenone-type benzoxazine during the thermal curing process.
[0062] The curing reaction process of the benzophenone-type benzoxazine monomer is as follows:
[0063]
[0064] The present invention also provides a composite membrane, comprising a matrix and a composite skeleton dispersed in the matrix;
[0065] The matrix includes fluorinated polyetheretherketone and polyetheretherketone;
[0066] The composite skeleton is the composite skeleton described in the above technical solution or a composite skeleton prepared by the preparation method described in the above technical solution.
[0067] In the present invention, the composite membrane includes a matrix, and the matrix includes fluorinated polyetheretherketone and polyetheretherketone; the mass ratio of the fluorinated polyetheretherketone and polyetheretherketone is preferably 1:0.25-4. In a specific embodiment of the present invention, the mass ratio of the fluorinated polyetheretherketone and polyetheretherketone can be 1:0.25, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5 or 1:4.
[0068] In the present invention, the ratio of the mass of the conductive coating in the composite film to the mass of the composite film after deducting the mass of the polybenzophenone-type benzoxazine is 0.05 to 0.35:1. In a specific embodiment of the present invention, the volume content of the composite skeleton can be 0.05:1, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1 or 0.35:1.
[0069] The present invention also provides a method for preparing the composite film according to the above technical solution, comprising the following steps:
[0070] Repeatedly mixing the composite skeleton with the dispersion of the matrix and then removing the solvent in the dispersion to obtain a composite;
[0071] The composite is formed into a shape to obtain the composite film.
[0072] In the present invention, the mixing is preferably performed under vacuum conditions.
[0073] In the present invention, the solvent preferably includes NMP.
[0074] In the present invention, the number of repetitions is preferably 3 times, the temperature of the removal is preferably 120° C., and the time is preferably 12 hours.
[0075] In the present invention, the molding process preferably includes preheating, wherein the preheating temperature is preferably 380° C. and the preheating time is preferably 10 min.
[0076] In the present invention, the molding pressure is preferably 50 MPa, the temperature is preferably 380° C., and the time is preferably 15 min.
[0077] After the molding, the pressure is preferably removed and the mixture is naturally cooled to room temperature.
[0078] The present invention also provides application of the composite film described in the above technical solution or the composite film prepared by the preparation method described in the above technical solution in thermal management.
[0079] The composite PBO fiber, composite skeleton and preparation method thereof, composite membrane and preparation method thereof and application provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0080] Figure 1 This is a flow chart for preparing MWCNTs&GnPs@PBO-PBZ / PEEK composite membrane material for example.
[0081] Example 1
[0082] Preparation of PBO-OH
[0083] In order to remove the sizing agent and contaminants on the surface of the PBO fiber, it was immersed in acetone and deionized water for 24 hours each. Finally, the surface-cleaned PBO fiber was placed in a vacuum oven at 60°C and dried for 4 hours. The cleaned PBO fiber was immersed in a watch glass with a certain content of ethanol solution, and the PBO fiber bundle was ultrasonically dispersed in an ultrasonic cleaner, and then dried in an oven.
[0084] The dispersed fibers were evenly fixed on a homemade glass rack: the plasma treatment instrument was used to activate the surface of the PBO fibers and increase their surface roughness. The treatment process parameters were set as follows: discharge power 120W, discharge time 360s, and vacuum chamber pressure 40Pa (P O2 :P Ar =3:2). After the plasma treatment, the fiber was taken out and put into use, and was recorded as PBO-OH fiber.
[0085] Preparation of continuous structure MWCNTs&GnPs@PBO-PBZ / PEEK composite membrane materials
[0086] The plasma-treated PBO fiber (1.4 g) was placed in a mixed solution of 2.5 g of benzophenone-type benzoxazine monomer and 100 mL of acetone and refluxed at 65 °C for 12 h.
[0087] Subsequently, 0.08 g of graphene nanosheets and 0.03 g of carbon nanotubes (8:3) were added to the above mixed solution. After cooling, the GnPs&MWCNTs@PBO-PBZ composite material was taken out and placed in an electric forced air drying oven for staged thermal curing to obtain a GnPs&MWCNTs@PBO-PBZ composite skeleton; a 30 mg / mL FPEEK / NMP solution was prepared, and an appropriate amount of PEEK ultrafine powder was added to the above solution for ultrasonication for 30 minutes to obtain a 150 mg / mL uniformly dispersed FPEEK / PEEK / NMP suspension (the mass ratio of FPEEK to PEEK is 1:4). The GnPs&MWCNTs@PBO-PBZ composite skeleton was immersed in the above-mentioned mixed dispersion, vacuum infused and heated at 120°C for 12 h to remove the NMP solvent, and this step was repeated 3 times. Then, it was preheated at 380°C for 10 min, and then heated at 50 MPa for 15 min. Finally, the pressure was removed and naturally cooled to room temperature to obtain a MWCNTs&GnPs@PBO-PBZ / PEEK composite material (size 4 cm×4 cm×0.2 mm).
[0088] Embodiments 2 to 7
[0089] The raw materials and amounts of Examples 2 to 7 are shown in Table 1, and the preparation method is the same as that of Example 1.
[0090] Comparative Examples 1 to 7
[0091] The only difference from Example 1 is that no benzophenone-type benzoxazine monomer is added. The raw materials and amounts of Comparative Examples 1 to 7 are shown in Table 1.
[0092] Table 1 Amount of each raw material in Examples 1 to 7 and Comparative Examples 1 to 7
[0093]
[0094] Note: Mass content = mass of carbon nanotubes and graphene nanosheets (conductive coating) / (mass of composite film - mass of PBZ)
[0095] Table 2 In-plane thermal conductivity and out-of-plane thermal conductivity of the composite film materials of Examples 1 to 7 and Comparative Examples 1 to 7
[0096]
[0097] Note: In-plane refers to the thermal conductivity of the sample in the horizontal direction; out-of-plane refers to the thermal conductivity of the sample in the vertical direction.
[0098] Thermal conductivity
[0099] The thermal conductivity of the MWCNTs & GnPs @ PBO / PEEK composite film materials of Comparative Examples 1 to 7 and the MWCNTs & GnPs @ PBO-PBZ / PEEK composite film materials of Examples 1 to 7 was measured by laser flash method. The results are as follows Figures 2-3 shown.
[0100] Depend on Figures 2-3 It can be seen that with the continuous increase of filler content, the thermal conductivity of the two composite membrane materials shows a similar trend of change, the thermal conductivity gradually increases, and the thermal conductivity of the composite membrane material with a continuous structure is higher than that of the composite membrane material with a random blending structure. The in-plane and out-of-plane thermal conductivities of the MWCNTs&GnPs@PBO-PBZ / PEEK composite membrane material of Example 7 are 32.01 W·m -1 K -1 and 3.05W·m -1 K -1 Compared with pure PEEK, the thermal conductivity growth rates are 13817% and 1226% respectively. The out-of-plane thermal conductivity of the random blended structure composite film material is 2.29 W·m -1 K -1 Much lower than the continuous structure composite membrane material (3.05W·m -1 K -1 ), which indicates that the continuous filler network structure and the introduction of PBZ jointly promote the improvement of the thermal conductivity of MWCNTs&GnPs@PBO-PBZ / PEEK composite film materials.
[0101] Electromagnetic shielding performance
[0102] The EMI shielding performance of MWCNTs&GnPs@PBO-PBZ / PEEK composite film material was measured by vector network analyzer in X-band. Figure 4 shown.
[0103] Depend on Figure 4 It can be seen that the absorption loss and reflection loss of the MWCNTs&GnPs@PBO-PBZ / PEEK composite film materials of Examples 1 to 7 show a trend of rapid increase, while the reflection loss of the composite film material increases slowly. The absorption loss and reflection loss of the MWCNTs&GnPs@PBO-PBZ / PEEK composite film material of Example 7 are 85.5dB and 15.9dB, respectively, which exceed the requirements of commercial shielding materials (20dB). In addition, the MWCNTs&GnPs@PBO-PBZ / PEEK composite film material in Example 7 obtains the best total shielding effectiveness value of 101.3dB, and the shielding effect reaches 99.999999993%.
[0104] Joule heating performance
[0105] When electricity is applied to a conductive material, the movement of electrons will be hindered, and the kinetic energy of the electrons will be converted into heat energy, which is called the Joule heating effect. The MWCNTs&GnPs@PBO-PBZ / PEEK composite membrane material of Example 7 has excellent conductivity. The continuous network formed by the carbon nanofillers (graphene nanosheets and carbon nanotubes) provides the necessary premise for the uniformity of Joule heating. The Joule heating performance of the circular composite membrane material with a diameter of 25.6 mm was studied as a model. The results are as follows: Figure 5 shown.
[0106] from Figure 5 It can be seen that when the DC power supply voltage is adjusted from 2 to 12V, the temperature of the composite film material is observed to rise rapidly, and it can be stabilized at the saturation temperature within 120s at different voltages. When the load voltage is 12V, the surface temperature of the composite film material reaches about 134.6℃, which is about 112.6℃ higher than the room temperature (22℃). The experimental results show that the MWCNTs&GnPs@PBO-PBZ / PEEK composite film material has excellent Joule heating performance at relatively low voltages and has great application potential in the field of personal thermal management.
[0107] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A composite PBO fiber, characterized in that: The invention comprises a PBO fiber and a polybenzophenone-type benzoxazine coated on the surface of the PBO fiber.
2. A composite skeleton, characterized in that: Comprising the composite PBO fiber of claim 1 and the conductive coating on the surface of the polybenzophenone-type benzoxazine; The conductive coating includes graphene nanosheets and carbon nanotubes.
3. The method for preparing the composite skeleton according to claim 2, characterized in that: The following steps are involved: The surface of the PBO fiber is treated with plasma to introduce hydroxyl groups on the surface of the PBO fiber to obtain PBO-OH fiber; The PBO-OH fiber, benzophenone-type benzoxazine and an organic solvent are first mixed, and the benzophenone-type benzoxazine is adsorbed on the surface of the PBO-OH fiber to obtain a first mixture; The first mixture is mixed with graphene nanosheets and carbon nanotubes, and the graphene nanosheets and carbon nanotubes are adhered to form a conductive coating to obtain a PBO-OH fiber containing a conductive coating and benzophenone-type benzoxazine; The PBO-OH fiber containing the conductive coating and benzophenone-type benzoxazine is thermally cured to obtain the composite skeleton.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the PBO-OH fiber to benzophenone-type benzoxazine is 1:0.25-12.
5.
5. The preparation method according to claim 3, characterized in that: The mass ratio of the graphene nanosheets to the carbon nanotubes is 1:0.1-1.
6. The preparation method according to claim 3, characterized in that: The thermal curing temperature is 130-210° C. and the time is 0.5-2 hours.
7. A composite membrane, characterized in that It includes a matrix and a composite skeleton dispersed in the matrix; The matrix includes fluorinated polyetheretherketone and polyetheretherketone; The composite skeleton is the composite skeleton described in claim 2 or a composite skeleton prepared by the preparation method described in any one of claims 3 to 6.
8. The composite membrane according to claim 7, characterized in that The ratio of the mass of the conductive coating in the composite film to the mass of the composite film minus the mass of the polybenzophenone-type benzoxazine is 0.05-0.35:
1.
9. The method for preparing the composite membrane according to claim 7 or 8, characterized in that: The following steps are involved: Repeatedly mixing the composite skeleton with the dispersion of the matrix and then removing the solvent in the dispersion to obtain a composite; The composite is formed into a shape to obtain the composite film.
10. Application of the composite film according to claim 7 or 8 or the composite film prepared by the preparation method according to claim 9 in thermal management.
Citation Information
Patent Citations
High-thermal-conductivity electromagnetic shielding polyether-ether-ketone composite material with isolation structure as well as preparation method and application thereof
CN113337077A
3D heat conduction network structure polyether-ether-ketone composite material and preparation method and application thereof
CN117986859A
Cited By
Heat conduction layer based on PBO fiber, copper-clad plate and preparation method and application of heat conduction layer and copper-clad plate
CN121949849A